Pengaruh Hedonic Value dan Utilitarian Value terhadap Customer Loyalty melalui Customer Satisfaction Pelanggan Richeese Factory Kota Bandung - Rachim, Salma Lutfiah; Marliani, Leni Evangalista (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to analyze the influence of Hedonic Value and Utilitarian Value on Customer Loyalty through Customer Satisfaction of Richeese Factory customers in Bandung City. This research involved designing a research instrument in the form of a questionnaire with the participation of 120 Richeese Factory customer respondents in Bandung City. The sample used was convenience sampling which is included in the nonprobability sampling technique. The data collection time in this study was classified as cross-sectional or one shot study. In this research, the validity and reliability of the instruments used were tested. The data analysis procedures used are descriptive analysis and verification analysis including multiple regression analysis and Sobel test. Of the seven research hypotheses proposed, all hypotheses are supported by empirical data. The results obtained are, Hedonic Value has a positive and significant relationship with Customer Satisfaction, Utilitarian Value has a positive and significant relationship with Customer Satisfaction, Hedonic Value has a positive and significant relationship with Customer Loyalty, Utilitarian Value has a positive and significant relationship with Customer Loyalty, Customer Satisfaction have a positive and significant relationship to Customer Loyalty, Hedonic Value to Customer Loyalty does not have a positive and significant relationship through Customer Satisfaction, Utilitarian Value to Customer Loyalty has a positive and significant relationship through Customer Satisfaction. It is hoped that the results of this research will provide benefits for further research and managers of the objects being assessed or similar fast food industries regarding designing strategies that are relevant to improving the quality of these attributes.